Critical Discourse Analysis of Norman Fairclough's Research Model in the Article "Selamat Tinggal Paspor Indonesia" - Jasmine Anggun Pratiwi (Communigate, 2025)
This article discusses how the structure of critical discourse analysis in Norman Fairclough's research model can dissect and analyze the ideology conveyed by the author through a newspaper article published in 'Kompas' on December 3, 2024. The method used for the analysis involves a functional approach, paying attention to the social and cultural contexts to uncover and understand the author's ideology and the context being conveyed through the article titled 'Selamat Tinggal Paspor Indonesia'. According to Norman Fairclough's model, the analysis is divided into three structural levels: microstructural, mesostructural, and sociocultural studies. Findings demonstrate how media discourse shapes public understanding of complex socio-economic issues, particularly regarding human capital flight and national development disparities between Indonesia and Singapore. This analysis contributes to our understanding of how media texts influence public perception of national identity and economic mobility in Southeast Asia.